If God is male then the male is God - PULP FICTIONS No.3 - Karin van Marle (Pretoria University Law Press (PULP), 2007)
If God is male then the male is God - PULP FICTIONS No.3 Edited by Karin van Marle 2007 ISSN: 1992-5174 Pages: 17 Print version: Available Electronic version: Free PDF available